Strongyloidiasis in a Puppy in Northeastern Brazil - Alves, Rodrigo Cruz; Soares, Yanca Góes dos Santos; Pinheiro, Jôvanna Karine; Brito Junior, João Ricardo Cruz; Silva, Raquel Annes Fagundes; Firmino, Millena de Oliveira; Galiza, Glauco José Nogueira de; Dantas, Antônio Flávio Medeiros (Acta Scientiae Veterinariae, 2021)
Background: Strongyloides stercoralis is a nematode that causes intestinal infection in vertebrate hosts, especially in humans and dogs. The species S. stercoralis is responsible for chronic and asymptomatic infections in adult dogs or serious infections in puppies and immunosuppressed animals. In Brazil, natural infection in dogs was demonstrated by coproparasitological and serological methods, however, there are no reports that address the clinicopathological characteristics of the infection in the canine species. Thus, this paper aims to describe the epidemiological, clinical and pathological aspects of S. stercoralis infection in a puppy in Northeastern Brazil. Case: A puppy female Chihuahua was referred to the Animal Pathology Laboratory of the Veterinary Hospital of the Federal University of Campina Grande for necropsy with a historic of severe respiratory symptoms and gastrointestinal changes that included sanguineous diarrhea and vomiting that evolved to death in 5 days. Grossly, there was a moderate amount of slightly reddish fluid in the thoracic cavity. The lungs remained expanded with a smooth, shiny, and diffusely reddish pleural surface interspersed with multifocal and blackened coalescent areas. Upon cutting, a moderate amount of slightly yellow foamy liquid flowed from the airways and trachea. In the duodenum, the mucosa was diffusely reddened. Histologically, there were multifocal to coalescent areas of moderate interalveolar accumulation of fibrin, edema and hemorrhage in the lung surrounded by an inflammatory infiltrate composed of foamy macrophages associated with numerous parasitic structures in longitudinal and transverse sections in the alveolar lumen and pleural surface. In the duodenum, we observed flattening with diffuse and moderate fusion of the villi and multifocal areas of mucosal erosion. The crypts were moderately dilated, covered by attenuated epithelium, with numerous longitudinal and transversal sections of adult nematode parasites, larvae and eggs associated with inflammatory lymphplasmocytic infiltrate in the lamina propria. The morphological characteristics were compatible with the nematode S. stercoralis. Discussion: The diagnosis of strongyloidiasis was performed by means of microscopic lesions associated with parasitic structures morphologically compatible with the nematode S. stercoralis. This species is responsible for parasitism especially in humans, dogs, and cats. Parasites are the only ones that have a life cycle that involve free living form and parasitic. In this case, it was not possible to determine the primary portal of entry for the infection, but most infections commonly occur through the penetration of the larvae into the skin or mucous membranes, where they migrate via the haematogenous to the lung, then they are swallowed up to the intestine. Occasionally, there is autoinfection by larvae that enter the intestinal mucosa or perianal region and the contamination of neonates and puppies through the ingestion of milk. The clinical signs evidenced in this case, revealed the committed respiratory and gastrointestinal, possibly may be related to the migration of the larvae in the lungs and the destruction of the intestinal epithelium caused by the high number of parasites, respectively. It is concluded that strongyloidiasis is an uncommon infectious disease in puppies in Brazil, capable of causing severe respiratory and gastrointestinal changes that result in the death of animals with a high parasitic load and should be included in the differential diagnosis of diseases that affect the respiratory system and gastrointestinal tract of dogs. Keywords: dog disease, parasitic infection, nematode, Strongyloides stercoralis.